Efeito de protocolos parciais na prevalência de gengivite e na associação entre gengivite e QVRSB em adolescentes de 12 anos do Sul do Brasil - Machado, Michely Ediani (2015)
The "gold standard" method for estimating the prevalence of periodontal disease and associated factors is the "full-mouth" evaluation. However, some difficulties inherent to the operational aspects difficult it s applicability. For this reason, partial periodontal protocols (PPP) have been often used. In addition, studies have incorporated the assessment of quality of life related to oral health (OHRQoL) to complement regulatory traditionally used measures. Objective: To compare the prevalence of gingival bleeding (GB) between different PPPs with the "full-mouth" (FM) and to assess the impact PPPs in the association between GB and OHRQoL. Methodology: This cross-sectional study assessed 1,134 teens from Santa Maria city public schools, RS, Brazil. GB was measured using the FM exam and nine different PPPs. A specific questionnaire was used to assess OHRQoL (Brazilian version of CPQ11-14) in order to estimate the impact of each PPP in the association between GB and OHRQoL. Result: "Full-mouth DV", "2Q DV" and "CPI" PPPs showed better overall accuracies for the prevalence of GB. For the OHRQoL the most of PPPs biased the FM results. Conclusion: The results suggest that "full-mouth" and "2Q diagonally partial mouth with evaluation of the "MV, VV and DV" sites have better performances for evaluation GB in the adolescents. For the OHRQoL associations, PPPs biased the FM results.